Exploring students' engagement through active learning in english as a second language (ESL) classroom - Rosnani, Ismail; Nurul Nadia, Muhammad; Siti Norzaimalina, Abd Majid (UPM, 2023)
Getting student to pay attention during a learning session is never easy. Most of the time, the instructor would be the only one doing the talking part without receiving any response. Only a few student, occasionally fewer than five, would reply. Everyone voice was only audible to the instructor once the class is over and they walked out to the door and said "Thank you, madam". Students' participant and engagement in class were not up to expectations.